Vascular endothelial growth factor inhibition and proliferative diabetic retinopathy, a changing treatment paradigm? - Wu, Lihteh (Taiwan J Ophthalmol, 2019)
Prior to the development of panretinal photocoagulation (PRP) in the 1970s, proliferative diabetic retinopathy (PDR) was the most common cause of blindness in diabetic patients. The diabetic retinopathy study demonstrated that PRP could decrease severe visual loss from PDR by 50%. Since then and for the past four decades, PRP has been the treatment of choice for eyes with PDR. In the past decade, vascular endothelial growth factor (VEGF) inhibition has become the treatment of choice for diabetic macular edema (DME). When treated intensively with anti-VEGF drugs, about one-third of eyes with DME experience an improvement in their diabetic retinopathy severity scale. Randomized clinical trials comparing ranibizumab to PRP and aflibercept to PRP have shown that VEGF inhibitors cause regression of intraocular neovascularization but need to be given on a fairly regular basis. Despite these promising results, concerns about treatment adherence have surfaced. Patients with PDR that are treated solely with anti-VEGF drugs and somehow interrupt their treatment are at a high risk of developing irreversible blindness. Combination treatment of PRP plus an anti-VEGF drug may be the treatment of choice for PDR.